If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 8A = 3A + 60 Reorder the terms: 25 + 8A = 60 + 3A Solving 25 + 8A = 60 + 3A Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-3A' to each side of the equation. 25 + 8A + -3A = 60 + 3A + -3A Combine like terms: 8A + -3A = 5A 25 + 5A = 60 + 3A + -3A Combine like terms: 3A + -3A = 0 25 + 5A = 60 + 0 25 + 5A = 60 Add '-25' to each side of the equation. 25 + -25 + 5A = 60 + -25 Combine like terms: 25 + -25 = 0 0 + 5A = 60 + -25 5A = 60 + -25 Combine like terms: 60 + -25 = 35 5A = 35 Divide each side by '5'. A = 7 Simplifying A = 7
| X^4+a^4+2a^2x^2=0 | | (2-x)=3-y | | 6d+9=2d+29 | | 7.4=t^2-4t-9.333 | | 12x^2+25x-208=0 | | -12=4(y+4)-8y | | 6-4(x+1)-3x=23 | | lnx^6=lnx^3+6 | | 9x=5x+27 | | 2(4+7)=3(8+X) | | 2+4x=-13+6 | | 7b+21=11 | | 7(b+3)=11 | | 6x+5=-2(x+1) | | 5(2x-1)=3(4x+2) | | 17+1p=7p-13 | | a(b-c)+b(c-a)= | | 8-x=5-6x | | -15x-5x=160 | | 2.5x+6=3x-4 | | x=5x-20 | | x-7x+4x=-30 | | 2x+4(50-x)=172 | | -7(2*-3-7)+4(2+5*-3)= | | 3(4n-1)+3=8n+16 | | -12x+15x=-21 | | 10v+6=46 | | 12n=8n+22 | | 10+6=46 | | 5d-27=3d-1 | | 3+4x=17+2x | | 7=4y+1 |